Identification of a possible proteomic biomarker in Parkinson’s disease: discovery and replication in blood, brain and CSF - Winchester, L; Barber, I; Lawton, M; Ash, J; Liu, B; Evetts, S; Hopkins-Jones, L; Lewis, S; Bresener, C; Malpartida, AB; Williams, N; Gentlemen, S; et al. (Oxford University Press, 2022)
Biomarkers to aid diagnosis and delineate progression of Parkinson’s Disease are vital for targeting treatment in the early phases of disease. Here, we aim to discover a multi-protein panel representative of Parkinson’s and make mechanistic inferences from protein expression profiles within the broader objective of finding novel biomarkers.